Hide or seek - Dobson, James C., 1936- (F.H. Revell Co, 1974)
This book deals with such questions as, what can parents do to protect their children from the agony of inferiority, how can teachers compensate for unfair value judgements and what can we do to build self-esteem in our children from infancy onward.